2008
DOI: 10.1074/jbc.m709037200
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Suppressor LATS1 Is a Negative Regulator of Oncogene YAP

Abstract: LATS (large tumor suppressor) or warts is a Ser/Thr kinase that belongs to the Ndr/LATS subfamily of AGC (protein kinase A/PKG/PKC) kinases. It is a tumor suppressor gene originally isolated from Drosophila and recently isolated from mice and humans. Drosophila or mice mutant for LATS develop tumors in various tissues. Recent studies in Drosophila demonstrate that LATS is a central player of an emerging tumor suppressor pathway called the Hippo-LATS/Warts pathway that suppresses tumor growth by regulating cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

23
775
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 710 publications
(801 citation statements)
references
References 54 publications
23
775
0
3
Order By: Relevance
“…PhosphoYap appeared with several upshifted bands, likely representing incremental phosphorylation of the five different Lats2 sites on Yap. 9,28 Analysis of mRNA by qPCR confirmed expression of the untagged Mst1 and WW45 ( Supplementary Figures 3a and b). Furthermore, qPCR showed that expression of endogenous CTGF, a target gene of Yap, increased with Yap overexpression, but was inhibited with Lats2, and was inhibited further when Lats2 was expressed together with Mst1 and WW45 (Figure 3b).…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…PhosphoYap appeared with several upshifted bands, likely representing incremental phosphorylation of the five different Lats2 sites on Yap. 9,28 Analysis of mRNA by qPCR confirmed expression of the untagged Mst1 and WW45 ( Supplementary Figures 3a and b). Furthermore, qPCR showed that expression of endogenous CTGF, a target gene of Yap, increased with Yap overexpression, but was inhibited with Lats2, and was inhibited further when Lats2 was expressed together with Mst1 and WW45 (Figure 3b).…”
Section: Resultsmentioning
confidence: 86%
“…Upon Hippo pathway activation, Lats phosphorylates Yap at Ser 127 . 9,28,29 In the densely plated cells, phosphorylation of Yap at Ser 127 was detected, demonstrating that the Hippo pathway was active (Figures 1b-d). To demonstrate that inhibition of apoptosis at high cell density was not cell type specific, we tested other cell lines.…”
Section: Resultsmentioning
confidence: 90%
“…Activated Lats1/2 in turn phosphorylate YAP/TAZ transcription co-activators on several residues (Dong et al, 2007;Zhao et al, 2007;Hao et al, 2008;Lei et al, 2008;Oka et al, 2008). Phosphorylation of S127 in YAP promotes 14-3-3 binding, resulting in cytoplasmic sequestration and therefore inactivation of YAP (Dong et al, 2007;Zhao et al, 2007;Hao et al, 2008;Lei et al, 2008;Oh and Irvine, 2008). Indeed, mutation of S127 and disruption of 14-3-3 binding lead to activation of YAP (Zhao et al, 2007), confirming the inhibitory nature of this phosphorylation.…”
Section: The Mammalian Hippo Pathwaymentioning
confidence: 99%
“…CTGF alone, however, does not account for all YAP phenotypes. YAP and TAZ also induce the expression of AREG (Zhang et al, 2009b) and FGF1 (Hao et al, 2008), which may also mediate non-cell-autonomous function of the Hippo pathway. However, the mechanisms underlying the induction of these genes, including the responsible transcription factors, are mostly unclear.…”
Section: The Mammalian Hippo Pathwaymentioning
confidence: 99%
“…9 Through these mechanisms the transcriptional activity of YAP is downregulated under conditions of high cell density. 6,10 Although many studies on the nonreceptor tyrosine kinase c-Abl (Abelson murine leukemia viral oncogene) are focused on its role as an oncogene as part of the fusion protein BCRAbl, 11 it is also known to play a role in the DNA damage response. 12 Once activated, c-Abl can promote apoptosis or induce cell cycle arrest through the phosphorylation and activation of p73, 13,14 a p53 paralog.…”
mentioning
confidence: 99%